Hidden in plain sight: Morphological and phylogenetic evidence for Bouteloua arizonica, a species distinct from Bouteloua aristidoides (Poaceae, Chloridoideae) - Cuellar-Garrido, Luis Fernando (Plant Divers, 2020)
Two varieties of Bouteloua aristidoides have been recognized, the widespread var. aristidoides and the more narrowly distributed var. arizonica. The two varieties differ in inflorescence form even more than that seen between many other closely related species of Bouteloua. We therefore asked whether these taxa might be better regarded as distinct species. A total of 93 vouchers were studied by using morphometry (principal components analysis and statistical tests), leaf micromorphology, ancestral state reconstruction, and/or molecular (ITS, trnC-rpoB and trnT-L-F) phylogenetic analyses. Except from the ITS tree, all results supported elevation of B. aristidoides var. arizonica to the rank of species, thus the new combination Bouteloua arizonica (M.E. Jones) L.F. Cuellar & Columbus comb. nov. et stat. nov., is proposed. Chloroplast and combined chloroplast-nuclear molecular trees depicted var. arizonica as monophyletic (even in sympatric populations with var. aristidoides) and reveals phylogenetic structure within var. aristidoides for which the presence of new undescribed varieties of B. aristidoides (different from B. arizonica) is addressed. B. arizonica differs from B. aristidoides in having fewer branches per inflorescence, a bigger branch with more spikelets, and a shorter branch extension. Scanning electron microscopy revealed the presence of papillae on leaves of B. arizonica as a clear synapomorphy. Growing mature plants of B. arizonica from seeds in a greenhouse revealed a strong cleistogamous nature for this species for which gene flow in sympatric populations with B. aristidoides seems unlikely. A taxonomic treatment and distribution map for identification of B. arizonica is provided.